2014
DOI: 10.1021/jf500231t
|View full text |Cite
|
Sign up to set email alerts
|

Daidzein Suppresses Tumor Necrosis Factor-α Induced Migration and Invasion by Inhibiting Hedgehog/Gli1 Signaling in Human Breast Cancer Cells

Abstract: In breast cancer, the cytokine tumor necrosis factor-α (TNF-α) induces cell invasion, although the molecular basis of it has not been clearly elucidated. In this study, we investigated the role of daidzein in regulating TNF-α induced cell invasion and the underlying molecular mechanisms. Daidzein inhibited TNF-α induced cellular migration and invasion in estrogen receptor (ER) negative MCF10DCIS.com human breast cancer cells. TNF-α activated Hedgehog (Hh) signaling by enhancing Gli1 nuclear translocation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…However, the irresponsiveness of TNF-α on CCA cell line (KKU-100) proliferation is still unclear and needs further investigation. Additionally, TNF-α can facilitate cancer cell invasion and has been investigated in breast cell lines (Ryu et al, 2011) and glioma cell lines (Bao et al, 2014). The results of our invasion assay supported that TNF-α also affected invasiveness of CCA cell line with dose-and time dependence.…”
Section: Discussionsupporting
confidence: 75%
“…However, the irresponsiveness of TNF-α on CCA cell line (KKU-100) proliferation is still unclear and needs further investigation. Additionally, TNF-α can facilitate cancer cell invasion and has been investigated in breast cell lines (Ryu et al, 2011) and glioma cell lines (Bao et al, 2014). The results of our invasion assay supported that TNF-α also affected invasiveness of CCA cell line with dose-and time dependence.…”
Section: Discussionsupporting
confidence: 75%
“…Consistent with this, Hh regulation of cell motility and inhibition of cell migration by blocking Hh signaling have been documented under various pathophysiological circumstances. [42][43][44][45] Overall, Hh signaling could be a therapeutic target for reduction of HSC activation and inhibition of profibrogenic behaviors of activated HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant Hh activation has been demonstrated in breast, colon, and prostate cancer (10)(11)(12), and is closely associated with self-renewal, invasion and migration of cancer stem cells, promoting cancer progression (13,14). It was reported that Hh signaling might induce EMT in pancreatic cancer (9,15).…”
Section: Introductionmentioning
confidence: 99%